Modern strategy and tactics development algorithm of internet marketing on the B2B market - Boiko, Natalia (Ekonomika rozvytku (Online), 2023)
In the modern economy, there are accelerated processes of transformation of business models that support the trends of economic globalization development. The relevance of the study is due to the need to model the marketing activities of enterprises, to follow consistent, both strategic and tactical, steps, especially in the B2B sector that have entered the online market, to improve the marketing performance of the enterprise and effectively achieve its strategic goals. The purpose of the article is to study the peculiarities of Internet marketing in the B2B segment and to determine the main strategic and tactical steps of its implementation. According to the method of scientific abstraction, the dependence between the toolkit for Internet promotion and the effect of its implementation in the activities of enterprises in the B2B sphere was revealed. Also, analysis and synthesis are used as methods of research in which a complex economic process or system is divided into constituent parts, elements, and subsystems, and all of them are studied separately. The work used a synergistic approach in research. The article analyzed the facts and investigated the state of the use of Internet marketing tools in the global B2B market. The result of the work is to propose the design of a modern algorithm for the development of Internet marketing strategies and tactics in the B2B market. These will allow enterprises of the B2B sector to choose efficient modern Internet marketing tools, taking into account their characteristics and the characteristics specifics of customers. The practical value of the algorithm lies in the fact that a logically consistent, connected, and timely set of steps for Internet promotion stimulates sales managers and, accordingly, affects the results of their activities, helps marketing managers and managers to make the company the most competitive and successful in its segment